Trichomoniasis - are we giving the deserved attention to the most common non-viral sexually transmitted disease worldwide? - Menezes, Camila Braz (Microb Cell, 2016)
Etiology: Trichomonas vaginalis is the etiologic agent of trichomoniasis, the most common non-viral sexually transmitted disease (STD) in the world. Transmission: Trichomoniasis is transmitted by sexual intercourse and transmission via fomites is rare. Epidemiology, incidence and prevalence: The WHO estimates an incidence of 276 million new cases each year and prevalence of 187 million of infected individuals. However, the infection is not notifiable. Pathology/Symptomatology: The T. vaginalis infection results in a variety of clinical manifestations - in most cases the patients are asymptomatic, but some may develop signs typically associated to the disease. Importantly, the main issue concerning trichomoniasis is its relationship with serious health consequences such as cancer, adverse pregnancy outcomes, infertility, and HIV acquisition. Molecular mechanisms of infection: To achieve success in parasitism trichomonads develop a complex process against the host cells that includes dependent- and independent-contact mechanisms. This multifactorial pathogenesis includes molecules such as soluble factors, secreted proteinases, adhesins, lipophosphoglycan that culminate in cytoadherence and cytotoxicity against the host cells. Treatment and curability: The treatment with metronidazole or tinidazole is recommended; however, cure failures remain problematic due to noncompliance, reinfection and/or lack of treatment of sexual partners, inaccurate diagnosis, or drug resistance. Therefore, new therapeutic alternatives are urgently needed. Protection: Strategies for protection including sexual behavior, condom usage, and therapy have not contributed to the decrease on disease prevalence, pointing to the need for innovative approaches. Vaccine development has been hampered by the lack of long-lasting humoral immunity associated to the absence of good animal models.